PENGHARAPAN MESIANIK DI DALAM KITAB ESTER MELALUI PENDEKATAN TEOLOGIS-AKROSTIK-PLOT - Sonny Zaluchu; Nur Juniati Waruwu; Eirene Kardiani Gulo (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
This research intends to reveal the concept of messianic hope contained in the book of Esther. The approach is taken to explain this is the search for theological meaning, the use of acrostic hermeneutics, and the use of narrative content. The results of the three approaches show that the Book of Esther is not just a historical romance but a way of working God in human life to save, and His intervention in shaping the history of His people. This book strongly echoes the messianic hope through the rescue and preservation of the Jewish people in the territory of the Persian empire. The plot is the same as God's great plan to send Jesus into the world to save people from the eternal punishment of sin.